Comparison of physical workload in upper extremities between left- and right-hand ultrasound scanning. (September 2022) - Tetteh, Emmanuel; Wang, Tianke; Norasi, Hamid; Bremer, Merri; Schmida, Elizabeth; Kim, Joseph; Koenig, Jordyn; Fortune, Emma; Kane, Garvan; Susan Hallbeck, M.
Ames, IA Cardiac sonographers suffer from high prevalence of work-related upper extremity musculoskeletal pain due to awkward postures and fatigue accumulation. Sonographers can choose either left- or right-hand scanning, or alternate between both, however, the impact of each scanning technique on the upper extremity muscles remains unknown. Four ambidextrous cardiac sonographers performed between four to six cardiac scans using left- and right-hand while postural and muscle activity were collected from specific muscles on the upper extremities. A comparison of the posture showed that apart from forearm pitch and 90 th percentile upper arm deviation, upper extremity postures between the two scanning techniques did not differ significantly. Furthermore, while right-hand scanning (RHS) appeared to induce slightly higher muscle activity in the deltoids compared to left-hand scanning (LHS), the difference between the two techniques was not significant. We recommend alternating between these two techniques to distribute muscle stress evenly to prevent muscle overuse.